Aktivitas Antibakteri Ekstrak Jeruju (Acanthus ilicifolius) terhadap Pertumbuhan Vibrio harveyi Secara in vitro (ANTIBACTERIAL ACTIVITY OF JERUJU (ANACTHUS ILICIFOLIUS) EXTRACTS ON THE GROWTH OF VIBRIO HARVEYI IN VITRO) - Saptiani, Gina; Prayitno, Slamet Budi; Anggoro, Sutrisno (Jurnal Veteriner, 2013)
The aim of this research was to study the potential of jeruju (Acanthus ilicifolius) extract as anantibacterial for alternative therapy and control of bacterial diseases in prawn nurseries. Ethanol extractionwas prepared from jeruju’s leaves, trunks, fruits, and flowers..Each extract was prepared at differentconcentrations (50 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm,900 ppm, and 1000 ppm, respectively) and further tested its antibacterial activity against Vibrio harveyiusing the agar disc diffusion method. The results showed that A. ilicifolius is a potential antibacterial,extract of the leaves seemed to be more effective in inhibit the growth of V. harveyi compared to other partsof the plant.
Keywords: jeruju extract, Acanthus ilicifolius, Vibrio harveyi.